Pengaruh Biaya Pemeliharaan Terhadap Pendapatan Rawat Inap Periode 2016-2018 (Studi kasus pada Klinik Nafila Medika Karawang) - Wirman Wirman; Muhammad Nasim Harahap; Ayu Putri (Badan Penerbit Fakultas Ekonomi dan Bisnis Universitas Singaperbangsa Karawang, 2022)
The purpose of this research is to determine the effect of maintenance costs on inpatient income. This research was conducted to the clinic Nafila Medika Karawang in 2016-2018. The hypothesis in this study is that maintenance costs have an influence on inpatient incomes. Hypothesis testing was conducted with two-party trials using the T student formula. The hypothesis testing conducted is comparing t count =-3.282 with-t table – 2.030 (? = 0.05), because T counts smaller than-t tables, so hypotheses that state maintenance costs affect the inpatient income received. From the statistical calculation results indicate a negative relationship between the maintenance cost to the hospitalisation. And the resulting coefficient of determination is 24.1% which means that the cost of influence of maintenance cost to inpatient income is 24.1%, the remaining 75.9% is influenced by other variables that have not been studied in this research.